Spatial Localization of EEG Electrodes in a TOF+CCD Camera System - Chen, Shengyong; He, Yu; Qiu, Huili; Yan, Xi; Zhao, Meng (Frontiers in Neuroinformatics, 2019)
A crucial link of electroencephalograph (EEG) technology is the accurate estimation of EEG electrode positions on a specific human head, which is very useful for precise analysis of brain functions. Photogrammetry has become an effective method in this field. This study aims to propose a more reliable and efficient method which can acquire 3D information conveniently and locate the source signal accurately in real-time. The main objective is identification and 3D location of EEG electrode positions using a system consisting of CCD cameras and Time-of-Flight (TOF) cameras. To calibrate the camera group accurately, differently to the previous camera calibration approaches, a method is introduced in this report which uses the point cloud directly rather than the depth image. Experimental results indicate that the typical distance error of reconstruction in this study is 3.26 mm for real-time applications, which is much better than the widely used electromagnetic method in clinical medicine. The accuracy can be further improved to a great extent by using a high-resolution camera.